Analisa Materialisme dalam Novel The Great Gatsby dan Pengaruhnya terhadap Moralitas Tokoh Berdasarkan Teori Kritis Baru - Putri, Amira Khairianda (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2024)
A research study is made on the issue of materialism in F. Scott Fitzgerald's novel The Great Gatsby and its influence on the morals of the characters. Through a qualitative analysis of primary and secondary data, this study examines key characters' actions and motivations, such as Jay Gatsby, Daisy Buchanan, and Tom Buchanan The technique is based on the New Criticism doctrine, which emphasizes textual analysis. The key conclusions focus on how money and materialism impact the characters' moral behavior. This research is crucial for interpreting the moral message in literary works and investigating wider implications about materialism.